The Influence of Net Profit Margin and Company Size on Financial Performance in Product Sub-Sector Companies Registered Households on BEI 2021-2023 - Rizka Fazria; Salsabila Azzahro Lubis; Alma Hafsa Fadilah; Intan Afriliyani; Dio Jeremia Sembiring; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This research investigates how profitability and company size affect financial performance among household product companies listed on the Indonesia Stock Exchange from 2021 to 2023. Employing a quantitative methodology with multiple linear regression, the study analyzes 27 samples selected through purposive sampling. The analysis reveals that Net Profit Margin, as a measure of profitability, significantly impacts financial performance, demonstrated by a regression coefficient of 0.244 and significance level of 0.003 (p < 0.05). Similarly, company size shows a significant influence with a regression coefficient of 0.210 and significance level of 0.000 (p < 0.05). When examined together, both factors demonstrate substantial impact on financial performance, supported by an F-value of 19.350 and significance level of 0.000 (p < 0.05). These results suggest that companies maintaining higher profitability levels and larger operational scales typically achieve superior financial performance. Based on these findings, the study recommends that management focus on improving operational efficiency and strategic business expansion to maximize performance outcomes.